Technology-Skill Complementarity in the Early Phase of Industrialization - Raphaël Franck; Oded Galor (Institute for the Study of Labor (IZA), 2016)
The research explores the effect of industrialization on human capital formation. Exploiting exogenous regional variations in the adoption of steam engines across France, the study establishes that, in contrast to conventional wisdom that views early industrialization as a predominantly deskilling process, the industrial revolution was conducive for human capital formation, generating broad increases in literacy rates and educational attainment.
Keywords: N33; N34; O14; O33; 330; technology-skill complementarity; economic growth; industrialization; human capital; steam engine